The Contributions of Clinical Pharmacology to HIV Cure Research. Issue 2 (18th April 2021) - Fletcher, Courtney V.; Dyavar, Shetty Ravi; Acharya, Arpan; Byrareddy, Siddappa N.
Abstract : Combination antiretroviral therapy (ART) can suppress plasma HIV‐RNA to < 50 copies/mL, decrease HIV transmission, reduce mortality, and improve quality of life for people living with HIV. ART cannot, however, eliminate HIV from an infected individual. The primary barrier to cure HIV infection is the multiple reservoir sites, including adipose tissue, bone marrow, central nervous system, liver, lungs, male and female reproductive system, secondary lymph nodes, and gut‐associated lymphoid tissue, established 1 to 2 weeks after acquisition of HIV. Additional challenges include understanding the mechanism(s) by which HIV is maintained at low or undetectable levels and developing treatments that will eradicate or produce a sustained suppression of virus without ART. To date, the most extensive clinical investigations of cure strategies have been the shock‐and‐kill approach using histone deacetylase inhibitors (HDACis) to induce reactivation of latent HIV. Despite evidence for HIV latency reversal, HDACis alone have not decreased the size of the latent reservoir. Clinical pharmacologic explanations for these results include a low inhibitory quotient (i.e., low potency) within the reservoir sites and intrinsic (e.g., sex differences and reservoir size) and extrinsic (physiochemical and pharmacokinetic drug characteristics) factors. We offer an outline of desired clinical pharmacologic attributes for therapeutics intended for clinical HIV cure research and call for research teams to have early and ongoing involvement of clinical pharmacologists. We believe such a collective effort will provide a solid scientific basis and hope for reaching the goal of a cure for HIV infection.